2018
DOI: 10.1002/14651858.cd012964
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytic drugs for treating primary postpartum haemorrhage

Abstract: TXA when administered intravenously reduces mortality due to bleeding in women with primary PPH, irrespective of mode of birth, and without increasing the risk of thromboembolic events. Taken together with the reliable evidence of the effect of TXA in trauma patients, the evidence suggests that TXA is effective if given as early as possible.Facilities for IV administration may not be available in non-hospital settings therefore, alternative routes to IV administration need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 47 publications
4
68
0
10
Order By: Relevance
“…Indeed, for women and babies who do have diseases or complications, this type of research is critical. For example, the evidence on the efficacy of magnesium sulphate to prevent pre-eclampsia and to treat eclampsia [14] and the use of tranexamic acid for catastrophic haemorrhage [15] have saved many lives around the world. However, the large majority of the 130 million women who give birth annually do not require medical procedures or pharmacological agents to safely complete a process that has been shaped by complex adaptive evolution-a process that is critical to the survival of the human race.…”
Section: Current Norms In Childbirth and Related Researchmentioning
confidence: 99%
“…Indeed, for women and babies who do have diseases or complications, this type of research is critical. For example, the evidence on the efficacy of magnesium sulphate to prevent pre-eclampsia and to treat eclampsia [14] and the use of tranexamic acid for catastrophic haemorrhage [15] have saved many lives around the world. However, the large majority of the 130 million women who give birth annually do not require medical procedures or pharmacological agents to safely complete a process that has been shaped by complex adaptive evolution-a process that is critical to the survival of the human race.…”
Section: Current Norms In Childbirth and Related Researchmentioning
confidence: 99%
“…Aware of the forthcoming WOMAN Trial findings, the Guideline Steering Group prioritised this question for urgent updating. A new Cochrane review of antifibrinolytics for PPH treatment was rapidly initiated 61 as an offshoot of the existing Cochrane review on PPH treatments 62. The new review identified only two trials that compared the use of any fibrinolytic drug with no treatment in women with PPH, and findings were dominated by the WOMAN Trial 60.…”
Section: Step 5: Developing Recommendations With a ‘Living’ Guidelinementioning
confidence: 99%
“…However, the evidence for the timing and nature of surgical interventions is mostly from expert opinion or based on case series which are included as the evidence. 24,25,26,27,28 Most evidence for success of balloon tamponade, which is widely used, is based on case reports but two recent RCTs suggest lack of efficacy and increased risk of adverse outcomes. 25,30 Balloon tamponade is included in the algorithm pending more research with the proviso that it should be a temporising rather than therapeutic measure and abandoned if it fails to control bleeding within 20 minutes.…”
Section: 35mentioning
confidence: 99%
“…Similarly, laparotomy and further surgical measures are required, as already described for algorithm 2, if medical and BT fails to control the bleeding. 16,17,18,19,20,26,27,28,35,43 If MROP is complicated due to morbid adherence, it may require uterine curettage under ultrasound, specialist advice and assistance if available; and laparotomy for conservative surgical measures or hysterectomy, if the skill is available.…”
Section: 35mentioning
confidence: 99%